Crimean Tatar-Danish diplomacy in the documents of the Crimean Khanate. Part 2 - Refat Abduzhemilev (Крымское историческое обозрение)
The rubric presents original in language and style yarlyks and letters of the Crimean Khanate’s ruling elite, with the translation into Russian, reflecting the Crimean Tatar-Danish contacts in the 17th century (Latinographic transliteration and translation by R. R. Abduzhemilev). Materials were collected from the stocks of the Reichsarchives (Imperial Archives) in Copenhagen (Denmark) and they were published by Josef Matuz in a book “Krimtatarische Urkunden im Reichsarchiv zu Kopenhagen: Mit historisch-diplomatischen und sprachlichen Untersuchungen”. Freiburg: Klaus Schwarz Verlag, 1976. 348 +34 s. [“Crimean Tatar Documents in the Reichsarchives in Copenhagen: with Historical– Diplomatic and Linguistic Researches”. Freiburg: Klaus Schwartz Verlag, 1976. 348+34 p.].